Consumer Response Analysis to Food Quality of Fermented Cassava Ice Cream - Hertanti, Lani Felicia (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2022)
Ice cream is a frozen product made from processed milk, cream, and a combination of various ingredients that are liked by various groups. Ice cream is proven to have some unexpected nutritional facts. The advantages of ice cream are supported by its main ingredients, namely nonfat milk and milk fat. Meanwhile, cassava tape results from cassava fermentation by yeast which contains mould, yeast, lactic acid bacteria, and amylolytic bacteria. This research is an experimental type that aims to analyze people's preference for cassava tape ice cream quality based on aspects of colour, appearance, texture, aroma, and taste, tested on 34 respondents. The analytical method used was the hedonic test with a Likert scale with 4 levels (Like, Like, Like, Dislike, Really Dislike) through questionnaires and organoleptic tests through short interviews with 3 respondents on each aspect. The results showed that through the hedonic test, the colour aspect was very liked with a value of 3.97, the appearance aspect was very liked with a value of 3.94, the texture aspect was very liked with a value of 3.88, the aroma aspect was very liked with a value of 3.47, and the taste aspect gets the very like category with a value of 3.50. Meanwhile, through the organoleptic test, the 3 respondents in each aspect liked all the aspects tested. Based on the study's results, it can be concluded that tape cassava ice cream is liked by respondents based on aspects of colour, appearance, texture, aroma, and taste.